1. Use the factor theorem to factorise completely f(x)= x³+x²-4x-4. Hence solve the equation x³+x²-4x-4=0 f(x) = x³ + x² - 4x - 4 f(x) = (x³ + x²) - (4x + 4) f(x) = x²(x + 1) - 4(x + 1) f(x) = (x + 1)(x² - 4) f(x) = (x + 1)(x² - 2²) f(x) = (x + 1)(x + 2)(x - 2) x³ + x² - 4x - 4 = 0 (x + 1)(x + 2)(x - 2) = 0 Hi I was wondering if someone can help me with this assignment question, I did it and handed it in to my tutor and this is the feedback he gave me. He said I haven't applied the factor theorum correctly and factorised it with out using factor theorum where have I gone wrong? (These are my tutors comment) The start. Initially you had f(x) =x³+x²-4x-4. Then checking you find f(-1) = 0. Hence f(x)=(x+1)g(x) and work out what g is. And repeat for g(x). It's not the easiest way to do it. And your method would probably be the best way to go about it but the task says "Use the factor theorem".